2020
DOI: 10.4054/mpidr-wp-2020-010
|View full text |Cite
|
Sign up to set email alerts
|

Do income and marriage mediate the relationship between cognitive ability and fertility? Data from Swedish taxation and conscriptions registers for men born 1951-1967

Abstract: Working papers of the Max Planck Institute for Demographic Research receive only limited review. Views or opinions expressed in working papers are attributable to the authors and do not necessarily reflect those of the Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…For women, a higher social status was associated with a decreased likelihood of having children. Combined with previous studies showing that the social status-fertility relationship is primarily driven by the high risk of childlessness among lower social status men (Kolk and Barclay 2021), the current results suggest that social status, in terms of income and standardized education level, positively contributes to men's but not women's reproduction. This is done through mating success and a better chance at transitioning to parenthood instead of having more offspring in an industrialized societal setting.…”
Section: Effects Of Social Status On Mating and Reproductive Successsupporting
confidence: 75%
See 1 more Smart Citation
“…For women, a higher social status was associated with a decreased likelihood of having children. Combined with previous studies showing that the social status-fertility relationship is primarily driven by the high risk of childlessness among lower social status men (Kolk and Barclay 2021), the current results suggest that social status, in terms of income and standardized education level, positively contributes to men's but not women's reproduction. This is done through mating success and a better chance at transitioning to parenthood instead of having more offspring in an industrialized societal setting.…”
Section: Effects Of Social Status On Mating and Reproductive Successsupporting
confidence: 75%
“…Fieder and Huber (2007) found that income was positively associated with reproductive success for men, mainly because they could reduce the risk of childlessness; after excluding men who had no children, the positive association between social status and reproductive success for men became non-significant. Similar relationships between social status and bachelorhood, as well as childlessness, were found in contemporary Sweden (Kolk and Barclay 2021). Hu (2020) found that the positive relationship between men's social status and the number of offspring in historical China became non-significant after controlling for the number of marriages.…”
Section: Social Status Influences Mating and Reproductive Successmentioning
confidence: 71%
“…While it is quite plausible to hypothesize that cognitive abilities evolved as an adaptation, there is an ongoing debate whether intelligence is adaptive in contemporary humans, due to a mismatch between adaptations and environment. This debate is reflected in empirical data as well: both negative (Reeve et al, 2013;Shatz, 2008) and positive (Kolk & Barclay, 2021; associations were detected between the phenotypic scores of intellectual performance and fitness. Hence, examining the current evolution of intelligence remains an intriguing and exciting task.…”
Section: The Case Of Behavioral Traits-personality and Cognitionmentioning
confidence: 99%
“…A later study found a positive correlation between an index of ejaculate quality and facial attractiveness ratings (of the same Spanish men) provided by a different sample of men and women (Soler et al, 2014). Other research reports positive associations of intelligence with ejaculate quality (Arden, Gottfredson, Miller, & Pierce, 2009), male fertility (Kolk & Barclay, 2020), overall physical health (Arden, Gottfredson, & Miller, 2009), and height (Silventoinen et al, 2006; Sundet et al, 2005), suggesting that intelligence correlates with an overall fitness factor. However, not all research shows these positive correlations between phenotype quality and ejaculate quality.…”
mentioning
confidence: 98%